(untitled) (American Journal of Islam and Society, 2015)
The subject of Islamic geometric design has been described in numerous ways: Keith Critchlow’s Islamic Patterns and Syed Jan Abbas and Amer Shaker Salman’s Symmetries of Islamic Geometrical Patterns, both highly esoteric interpretations; Owen Jones’ Grammar of Ornament, Emile Prisse d’Avennes’ L’Art arabe d’apres les monuments du Kaire, and Jules Bourgoin’s Arabic Geometrical Pattern and Design, all descriptions of drawing collections; and even as a theme for countless “coffee table” books resplendent with glossy photographs of exotic patterns and colors. Is it fair to evaluate this book without tending to imagine the previous categories of this study? Years ago I led a course on this topic and desperately tried to juggle the beautiful, historic, and hands-on practical manifestations of the sacred through drawing particular geometric patterns over and over again. For this course I needed to select chapters, or portions of the abovementioned texts in addition to the comprehensive works of K. A. Creswell in Early Muslim Architecture, Doris Behrens-Abou Seif’s Mamluks of Cairo and Minarets of Cairo, as well as other architectural studies, and interpret and reconstruct the designs in order to teach them. It was a research project of sorts where the outcome was not textual but pedagogical. While reading this text by Eric Broug, I felt that he had gone through a similar but far more prolonged process. His book stands alone for several reasons: the author (1) weaves knowledge of the historical, recognition of the beautiful, and reconstruction of the practical regarding patterns. The succinct explanatory text, incredible detailed photography in situ, and clear stepby- step diagrams converge to elucidate this rich material; (2) outlines the influence of other artistic traditions and the development of a clear type of “Islamic geometry” that is easily recognizable; and (3) concentrates on the design approach of craftspeople, which was separate and concurrent with the scientific study of geometry. This difference is important: craftspeople applied geometric patterns to various surfaces and were concerned with aesthetic compositions; whereas scientists contemplated the complex patterns in terms of mathematical geometries ...